2019
DOI: 10.1093/cdn/nzz031.or34-07-19
|View full text |Cite
|
Sign up to set email alerts
|

Galactose and Sialo-galactose Modifications in Glycoproteins on the Surface of Bovine Milk Exosome Are Essential for Exosome Uptake in Non-bovine Species (OR34-07-19)

Abstract: Objectives Exosomes are natural nanoparticles that can be found in most body fluids including milk. Bovine milk exosomes (BME) are bioavailable and transfer cargos such as RNAs, lipids and proteins across species boundaries. Previous competitor studies implicated galactose-modifications in exosome surface proteins in exosome transport. The objectiveof our study was to assess the importance of glycan modifications in BME surface glycoproteins for BME uptake and distribution in human intestinal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…Furthermore, exosomes have been shown to confer protection against the adverse conditions present in the digestive tract, which suggests that the oral intake of these compounds facilitates the availability of their cargos [ 86 , 87 , 88 ]. Besides protecting their cargos, glycoproteins displayed in milk exosomes facilitate their recognition and uptake by the target cell receptors [ 70 , 89 ].…”
Section: Milk-derived Exosomesmentioning
confidence: 99%
“…Furthermore, exosomes have been shown to confer protection against the adverse conditions present in the digestive tract, which suggests that the oral intake of these compounds facilitates the availability of their cargos [ 86 , 87 , 88 ]. Besides protecting their cargos, glycoproteins displayed in milk exosomes facilitate their recognition and uptake by the target cell receptors [ 70 , 89 ].…”
Section: Milk-derived Exosomesmentioning
confidence: 99%
“…Multiple glycoproteins located on the surface of exosomes were examined, and their glycosylation profiles greatly affected the interactions of the exosomes with the acceptor cells . A previous report demonstrated that galactose and sialo-galactose modifications of glycoproteins on the surface of BMDEs facilitated the uptake of exosomes by nonbovine species . In contrast, the existence of mannose, N -acetylglucosamine, or lactose residues was reported to inhibit dendritic cells and macrophage internalization of exosomes. , …”
Section: Introductionmentioning
confidence: 99%
“…A study on bovine milk-derived EV uptake found that the glycans on membrane proteins of EVs determine their absorption on human intestinal cells and in mouse models [ 120 ]. Among the studied residues, galactose and N -acetylgalactosamine residues on EV proteins and N -acetylglucosamine residues on proteins of intestinal cells were important for EV uptake, as the removal of these glycans by enzymes or by knockout genes completely blocked EV uptake through the intestine and EV accumulation in the liver and pancreas [ 120 ]. EVs that had undergone desialylation were in general taken up more readily compared to normal EVs, but the increase varied between cell lines [ 121 ].…”
Section: Biochemical Properties Of Evs and Their Intrinsic Advantamentioning
confidence: 99%